Fibroepothelial polyp of the glans penis due to pad use for urinary incontinence - Kumsar, Şükrü (Canadian Medical Association, 2013)
A 78-year-old man was admitted to our urology polyclinic with painless penile mass. The lesion was 3.5 cm in size on the ventral aspect of the penis. He had been using a pad for urinary incontinance for 10 months and said that the lesion had been increasing in size for past 3 months. He underwent a wide local excision under local anesthesia. The histopathologic diagnosis was fibroepithelial polyp. A fibroepithelial polyp of the penis is very rare and strongly linked to long-term condom catheter use. We present a case of fibroepithelial polyp of the glans which is not associated with condom catheter use.